Influência da concentração alcalina (NaOH) e razão dos reagentes alcalinos (Na2SiO3/NaOH) em concreto álcali-ativado de base metacaulim - Silva Neto, José Anselmo da (2021)
Within the scope of the search for new sustainable materials that have greater mechanical performance, stability and durability than the binders traditionally used in the production of Portland concrete, alkali-activated materials appear as an option. These properties and attributes of alkali-activated composites are strongly related to the chemical reactions between the aluminosilicate and the alkali polyasylate that directly imply the properties of the mixture. Despite this, there is no standard dosing method for alkali-activated concrete, such as Portland concrete (ABCP, IPT, among others), and some of the few approaches in the literature are based on the trial and error method. In this work, the alkaline concentration (NaOH) and the ratio of alkaline reagents (Na2SiO3/NaOH) were identified as the main variables that affect the fresh, hardened and microstructural properties of these concretes with metakaolin. That said, the present dissertation aimed to evaluate the influence of alkaline concentration (NaOH) and alkaline reactants ratio (Na2SiO3/NaOH) on the fresh, hardened and microstructural properties of alkali-activated concretes based on metakaolin using 2k full factorial design. The experimental phase was divided into 5 (five) steps: characterization of materials (physical, chemical and mineralogical aspects); mixture planning (systematic literature review with the aid of the VOSviewer software and factorial design (2k ) for the two variables (NaOH and Na2SiO3/NaOH) with the support of the STATISTICA 10.0 software; preparation of the mixtures in accordance with the NBR 5738 standard (ABNT, 2015); analysis of fresh properties (setting times and slump test), hardened (compressive strength, tensile strength due to diametral compression, elasticity and dynamic damping, water absorption, void ratio and real density) and microstructural properties (SEM and XRD ); and, finally, the statistical modeling detecting the effects and interactions between the variables and their numerical reliability with a confidence interval of 95%. Different combinations for NaOH (8, 10, 12, 14 and 16 M) and ratios Na2SiO3/NaOH (1.0, 1.5, 2.0, 2.5 and 3.0) were evaluated. The effect of fresh properties in reference to setting times was more significant when increasing a higher alkaline concentration from 8 to 16 M for the same reason Na2SiO3/NaOH, reducing the initial and final setting time by 115 and 135 minutes mutually. In reference to the workability of these concretes, the increase in alkaline solutions in a combined form led to less workable composites, especially when intensifying the Na2SiO3/NaOH ratio from 1.0 to 3.0 using the same alkaline concentration, limited to approximately 72 mm. On the other hand, the agreed increase in the rate of alkaline dissolutions drastically improved the hardened properties, however, when exceeding the limit of 14 M for the same Na2SiO3/NaOH ratio, the compressive and tensile strength at 28 days were attenuated by 12.4 % and 11.5% respectively, as well as elasticity at 9.5% and actual density around 4%. Simultaneously, it was noticed that the increase in mechanical strength resulted in an inversely proportional behavior in relation to dynamic damping, as well as in water absorption and void ratio. The microstructural analysis proved that the alkali-activated composites regarding the action of the alkali concentration cannot show a low or high value for this alkali, since in both cases the complete efficiency of the dissolution of the aluminosilicates is impossible, thus resulting in reduced properties. Synchronically, the increase in the Na2SiO3/NaOH ratio was associated with a greater constitution of the three-dimensional network, indicating a greater degree of geopolymerization for any alkaline concentration. From another perspective, with regard to statistical modeling, the response surface models - ANOVA on all fresh and hardened properties were evaluated and statistically validated. Therefore, this optimization technique can reduce the time to find a suitable dosage, increasing reliability and achieving process robustness.